Application of a Scientific Approach with the Cognitive Domain to Improve Critical Thinking Ability of Elementary School Students - Ina Magdalena; Nisa Ayudhiya; Rahma Azzahrah Putri (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study discusses the application of a scientific approach with a focus on the cognitive domain as an effort to improve the critical thinking skills of elementary school students. The scientific approach emphasizes student-centered learning and involves exploration, observation and experimentation in the learning process. The cognitive domain on the other hand focuses on developing higher-order thinking skills such as analysis, synthesis, evaluation and reflection. Through the application of a scientific approach to the cognitive domain, students are given the opportunity to develop critical thinking skills from an early age. By applying the application of a scientific approach to the cognitive domain, it is hoped that elementary school students can develop their critical thinking skills effectively. This research hopes to provide practical insights and recommendations for educators and policy makers in an effort to improve the critical thinking skills of elementary school students.